DETERMINAN KONSUMSI ENERGI NEGARA ANGGOTA ORGANISASI KERJASAMA ISLAM - Rahmandani, Nadira; Sukmana, Raditya (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of economic growth, foreign direct investment, and trade openness on energy consumption in the Organization of Islamic Cooperation â€“ OIC countries from 2004 until 2014 simultaneously and partially. The study uses a qualitative method and employs panel data regression to analyze. The sample is taken by applying a purposive sampling technique and obtained 38 OIC countries. The empirical result shows that economic growth, foreign direct investment, and trade openness are simultaneously significant affecting energy consumption. Partially, economic growth and foreign direct investment have positive and significant effect on energy consumption while trade openness have negative and not significant effect on energy consumption.Keywords: Energy consumption, economic growth, trade openness, OIC countriesREFFERENCESAnto, M.B. Hendrie. 2003. Pengantar ekonomika Mikro Islami. Yogyakarta: Ekonisia.Antonio, Muhammad Syafiâ€™i. 2001. Bank Syariâ€™ah dari Teori ke Praktik. Jakarta: Gema Insani.Biro Pusat Statistik (BPS). 2008. Perkembangan Nilai Tukar Petani dan Harga Produsen Gabah, (online), (www.bps.go.id/getfile.php?news=319) diakses 17 Agustus 2017Burhansyah, Rusli dan Melia P. 2010.Kinerja Usaha Tani Padi dan Indikator Kesejahteraan Petani di Kubu Raya Kalimantan Barat, (Online), (www.pse.litbang.deptan.go.id)/ind/pdffiles/Pros_MP_15_2010.pdf) diakses 17 Agustus 2017Ghazaly, Abdul Rahman, dkk. 2010. Fiqh Muamalat. Jakarta: Prenada Media Group.Haroen, Nasrun. 2007. Fiqh Muamalah. Jakarta: Gaya Media PratamaHasan, M. Ali. 20004. Berbagai Macam Transaksi dalam Islam (Fiqh Muamalat). Jakarta: PT. Raja Grafindo Persada.Heryawan, Ahmad. 2009. â€œKesejahteraan dan Ukurannyaâ€. (Online). (http://ahmadheryawan.blogspot.co.id/kesejahteraan-dan-ukurannya). Diakses pada 3 februari 2017.Munawir, Ahmad Warson. 1997. Kamus Indonesia-Arab-Inggris. Surabaya: Pustaka ProgresifNasikun. 1993. Sistem Sosial Indonesia. Jakarta: Raja Grafindo PersadaPusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI). 2008. Ekonomi Islam. Jakarta: PT. Raja Grafindo Persada.Setiawan, Iwan. 2008. Alternatif Pemberdayaan Bagi Peningkatan Kesejahteraan Petani Lahan Kering (Studi Literatur Petani Jagung di Jawa Barat). Skripsi tidak diterbitkan. Bandung. Fakultas Pertanian Universitas Padjajaran.Sugiyono. 2010. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Syamsuddien, Darsyaf Ibnu. 1994. Darussalam: Prototype Negeri Yang Damai. Surabaya: Media Idaman Press.Yin, Robert K. 2009.Case Study Research Design and Methods.Fourth Edition. California: sage inc.